2021
DOI: 10.3390/plants10050905
|View full text |Cite
|
Sign up to set email alerts
|

Tremellomycetes Yeasts in Kernel Ecological Niche: Early Indicators of Enhanced Competitiveness of Endophytic and Mycoparasitic Symbionts against Wheat Pathobiota

Abstract: Tremellomycetes rDNA sequences previously detected in wheat kernels by MiSeq were not reliably assigned to a genus or clade. From comparisons of ribosomal internal transcribed spacer region (ITS) and subsequent phylogenetic analyses, the following three basidiomycetous yeasts were resolved and identified: Vishniacozymavictoriae, V. tephrensis, and an undescribed Vishniacozyma rDNA variant. The Vishniacozyma variant’s clade is evolutionarily close to, but phylogenetically distinct from, the V. carnescens clade.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Their prevalence in the upper layers of shallow disked-tilled soils could therefore be explained by their association with enriched crop residues that are retained in these soils, resulting in increased amounts of fungal substrates. Tremellomycetes, on the other hand, are yeasts with the ability to degrade complex compounds quickly and overcome anoxic events by fermentation (Yurkov, 2018;Vujanovic, 2021). The greater availability of labile C in less intensely tilled soils (Bongiorno et al, 2019) may promote copiotrophic fermenting yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…Their prevalence in the upper layers of shallow disked-tilled soils could therefore be explained by their association with enriched crop residues that are retained in these soils, resulting in increased amounts of fungal substrates. Tremellomycetes, on the other hand, are yeasts with the ability to degrade complex compounds quickly and overcome anoxic events by fermentation (Yurkov, 2018;Vujanovic, 2021). The greater availability of labile C in less intensely tilled soils (Bongiorno et al, 2019) may promote copiotrophic fermenting yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oscillating nutrient availability, phyllosphere yeasts also need to adapt to oscillating temperatures, which can differ drastically between day and night, winter and spring. Yeasts from the genera Sporobolomyces , Rhodotorula and Vishniacozyma have been proposed to tolerate extreme environmental conditions and to help plants adapting to cold environments ( Buzzini et al, 2018 ; Vujanovic, 2021 ). Our results showed that all isolates from these genera grew at different temperatures, including low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are wood, plant, lichen, or fruit surface fungi distributed in natural environments. Specifically, Vishniacozyma victoriae and Stereum hirsutum, detected in this study, are related with lichens, mosses, and plants [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%